Impacted canines: Clinical and therapeutical aspects - Cristian Olteanu; Viorica Tarmure; Laura Ordean; Eugen Bud; Manuela Chibelean; Mariana Pacurar (Romanian Journal of Stomatology, 2020)
Impacted canines represent an increasingly frequent anomaly, of particular importance for the functionality of the dentomaxillary system and aesthetic appearance. Aim. To present the incidence and the degree of impacted canine in a group of children aged who need an orthodontic treatment. Material and method. We conducted a study in 18 patients, who requested a treatment plan in the period 2014-2017. The materials used in the study were: patients’ medical records, the orthopantomographic radiographs, study models and photographs of each case. Results. The frequency of canine impaction following the study was 8%, more frequent involvement of the male sex, with a percentage of 56% compared to the female sex, with 44%. The most frequent degree of impaction found in this study was 2nd degree, followed by 3rd degree, and 1st degree. Conclusion. In the great majority of the cases, impaction was located in the maxillary arch. The most frequent location was palatal, 78%.